Glimpsing Indonesia’s Social Media Discourse: What Goes on During the Covid-19 Infodemic - Ronny, Rafi; Herdiansyah, Herdis; Panjaitan, Berton Suar Pelita (REiLA : Journal of Research and Innovation in Language, 2023)
The COVID-19 pandemic has led to an "infodemic", of false and true information circulating on social media platforms. This phenomenon has posed various challenges in implementing disaster management programs to mitigate the effects of the pandemic, both globally and specifically in Indonesia. This study seeks to investigate the public's perception of social media discourse during the COVID-19 infodemic in Indonesia. Both primary and secondary data were collected to gain a comprehensive understanding of the issue. The primary data was collected through a focused group discussion (FGD) method. Meanwhile, secondary data sources were gathered using a literature review of scholarly articles. Approximately 60 articles were selected from sources such as Google Scholar and PubMed, published between 2019 and 2022. The articles were selected based on their relevance of the topic discussion. The study used Critical Discourse Analysis by Fairclough and Wodak (1997) to analyze the data. Both of the data were then synthesized to glimpse how the infodemic has impacted various disaster management efforts across various parts of the country. The results revealed that the infodemic has worsened public perceptions of how the Indonesian government handles COVID-19 as well as disrupting various disaster management processes. The study finds that the infodemic's impact on the public's perception has resulted in misinformation hampering effective pandemic management efforts. By recognizing the severity of the infodemic and working to combat it, Indonesia can more effectively manage the COVID-19 pandemic and minimize its negative impact on the public.